1999
DOI: 10.1128/jcm.37.4.944-949.1999
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Accuracy and Repeatability of Identification of Food-Borne Pathogens by Automated Bacterial Identification Systems

Abstract: The performances of five automated microbial identification systems, relative to that of a reference identification system, for their ability to accurately and repeatedly identify six common food-borne pathogens were assessed. The systems assessed were the MicroLog system (Biolog Inc., Hayward, Calif.), the Microbial Identification System (MIS; MIDI Inc., Newark, Del.), the VITEK system (bioMérieux Vitek, Hazelwood, Mo.), the MicroScan WalkAway 40 system (Dade-MicroScan International, West Sacramento, Calif.)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2000
2000
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(8 citation statements)
references
References 22 publications
0
8
0
Order By: Relevance
“…The first‐generation VITEK BAC (Bacillus) card allowed identification of only 17 Bacillus species, but its performance was proven reliable in comparison with other phenotypic methods (Ibert et al. 1996; Odumeru et al. 1999).…”
Section: Introductionmentioning
confidence: 99%
“…The first‐generation VITEK BAC (Bacillus) card allowed identification of only 17 Bacillus species, but its performance was proven reliable in comparison with other phenotypic methods (Ibert et al. 1996; Odumeru et al. 1999).…”
Section: Introductionmentioning
confidence: 99%
“…Of these studies, those that addressed the accuracy and repeatability of identification found the accuracy of Biolog’s system ranged from 70% to 100% (Klingler et al. 1992; Odumeru et al. 1999).…”
Section: Introductionmentioning
confidence: 99%
“…In total, there are at least 90 published environmental studies that have used the Biolog system as a means to evaluate bacteria and the links to these publications can be found at http://www.biolog.com/ mID_bibliography.html. Of these studies, those that addressed the accuracy and repeatability of identification found the accuracy of Biolog's system ranged from 70% to 100% (Klingler et al 1992;Odumeru et al 1999).…”
mentioning
confidence: 99%
“…Although conventional phenotypic characterization methods (e.g., cellular and spore morphology, gram staining, and biochemical tests) are useful for initial identification and characterization of Bacillus and related genera (Logan and Berkeley, 1984), these methods may not provide the sensitive differentiation needed to facilitate tracking of contaminants through processing systems, particularly for the 16S ribosomal RNA (rRNA) group 3 bacilli (i.e., Paenibacillus spp. ; Pires and Seldin, 1997;Odumeru et al, 1999;Guinebretiere et al, 2001;Teng et al, 2003;Durak et al, 2006).…”
Section: Introductionmentioning
confidence: 99%